Learning to live with a chronic illness, without thinking about death - Oliveira, Abílio (2021)
Chronic diseases are characterized by continuous pain and suffering, affecting the personal well-being, emotional, family and social. Patients experience moments of disruption, in face of alterations or deformations in their body image, and the need to change their habits and social roles. Some patients accept their situation, having good practices of self-care, adapting to their limitations and seeing the future with hope, while others represent the disease with sadness, negativity, fear and worry. The suffering but particularly death, emerges as a possibility that they prefer to ignore. This study aims to contribute to the understanding of how patients perceive their chronic disease, as well as life and death. Data were collected through a focus-group conducted with the consent of ten participants - adult and aging patients with rheumatoid arthritis. Among the various questions discussed, we highlight these: 'How do you envisage your illness?', 'How do you feel towards life?', 'How does illness affect your life?', ' How do you envisage death?' All participants recognize the disease as incurable, associating it with suffering, loneliness and grief. Women complain especially of the limitations imposed by the disease, which hinder the achievement of household tasks, while men emphasize the constraints they experience at a professional level. Patients reveal resignation or intention to learn to live with a persistent pain, but they all tend to ignore death. They believe in therapy, although they see it as excessive and with a temporary effect. The most important thing they consider is to be alive, hoping to get better.